The Direct Catalytic Asymmetric Aldol Reaction - Trost, Barry M. (2010)
Asymmetric aldol reactions are a powerful method for the construction of carbon-carbon bonds in an enantioselective fashion. Historically this reaction has been performed in a stoichiometric fashion to control the various aspects of chemo-, diastereo-, regio- and enantioselectivity, however, a more atom economical approach would unite high selectivity with the use of only a catalytic amount of a chiral promoter. This critical review documents the development of direct catalytic asymmetric aldol methodologies, including organocatalytic and metal-based strategies. New methods have improved the reactivity, selectivity and substrate scope of the direct aldol reaction and enabled the synthesis of complex molecular targets